The Establishment of Field Intensity Model of Wireless Telemetry Signal in Man-made Forests - Yun-Jie Xu; Wei Zhang (Institute of Advanced Engineering and Science, 2013)
On the basis of the configuration characteristics of man-made forests, the spread model of wireless sensor signal in man-made forests has been simplified according to electromagnetic wave theory and Fermat principle. The man-made forests is decomposed into independent medium with four layers, the spread model is simplified into free space model, attenuation screen model and absorption screen model. The field intensity calculation formulas of UHF frequency range attenuation screen and absorption screen has been discussed, which provides basis for optimization layout of sensor and offers theoretical basis of other radio frequency communication research in man-made forests. DOI: http://dx.doi.org/10.11591/telkomnika.v11i3.2186